The promised Neverland. 7, Decision - Shirai, Kaiu (Shonen Jump manga., 2018)
The children of the Grace Field House orphanage must escape a macabre fate before it's too late. Life at Grace Field House is good for Emma and her fellow orphans. While the daily studying and exams they have to take are tough, their loving caretaker provides them with delicious food and plenty of playtime. But perhaps not everything is as it seems... After learning the truth of the world they find themselves in, the orphans finally make their way out of the forest. With their improved survival skills, Emma, Ray and the other children arrive at the location laid out in Minerva's hidden message. But awaiting them there is a new kind of challenge...